Aspects Bacteriologiques Des Infections Du Site Operatoire Au Centre Hospitalier Departemental Du Borgou A Parakou (Benin) - Adrien, Hodonou Montcho; Fany, Hounkponou; Alexandre, Allodé Salako; Romaric, Tobome Sêmêvo; Holden, Fatigba Olatoundji; Bio, Tamou Sambo; Dodji, Mensah Emile Antoine; Félix, Atakpa; Raphael, Akpata; Emilie, Bankolé; Yves, Dadjo; Delphin, Mêhinto Kouassi (European Scientific Journal, ESJ, 2016)
Objective : Describe the bacteriological aspects of surgical site infections (SSI) at the regional hospital centre Borgou. Methods : From a descriptive, prospective study from february 2013 to july 2014, about 603 patients operated during the recrutment period(six mounths), the bacteriological data of 44 cases of SSI diagnosed according to the criteria CDC/NHSN have been analysed. Results : The frequency of SSI was 7.3% of the operated (44/603). The superficial incisional infections were 6, the deep infections were 34 and the organ infections or infections of space were 4. The sampling culture of the liquid was negative with 12 cases (27.3%) and positive with 32 cases (72.7%). Two germs were isolated in two cases. The negative Gram germs were the most isolated with 22 cases (64.7%) of Escherichia coli. The multiresistance was noted with 14 cases out of 34 (41.2%). Conclusion : The negative Gram germs were those which predominate in the infections of the operating site at the regional hospital center Borgou. The high rate of resistance to usual antibiotics must raise preventive and hard actions in order to inflect the graph of frequency and protect the antibiotics.